1991
DOI: 10.1007/bf02219716
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of the SADS-LA in a family study setting

Abstract: The joint-rater and test-retest reliability study of two translated versions of the SADS-LA (Schedule for Affective Disorders and Schizophrenia--Lifetime version--modified for the study of anxiety disorders), one in French and the other in German, have been tested in family study settings, in a sample of patients and first-degree relatives. The test-retest reliability study demonstrated that identification of major affective disorders and schizophrenia was performed with sufficient reliability; however, diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 12 publications
1
54
0
Order By: Relevance
“…Family studies Bertelsen and Gottesman, 1995] have shown schizoaffective disorder to be in the familial spectrum of both schizophrenia and bipolar disorder, and probably bearing liability to both disorders . Moreover, the reliability of the schizoaffective diagnosis is low in several studies [Maziade et al, 1992;Hostetter et al, 1983;Leboyer et al, 1991;McGorry et al, 1990;Fennig et al, 1994]. Incidentally, Antonarakis et al [1995], Mowry et al [1995], and Moises et al [1995] also included schizoaffective disorder in the affection definition that yielded modest positive linkage trends at 6p24-22.…”
Section: Discussionmentioning
confidence: 92%
“…Family studies Bertelsen and Gottesman, 1995] have shown schizoaffective disorder to be in the familial spectrum of both schizophrenia and bipolar disorder, and probably bearing liability to both disorders . Moreover, the reliability of the schizoaffective diagnosis is low in several studies [Maziade et al, 1992;Hostetter et al, 1983;Leboyer et al, 1991;McGorry et al, 1990;Fennig et al, 1994]. Incidentally, Antonarakis et al [1995], Mowry et al [1995], and Moises et al [1995] also included schizoaffective disorder in the affection definition that yielded modest positive linkage trends at 6p24-22.…”
Section: Discussionmentioning
confidence: 92%
“…The French translation of the DIGS (Leboyer et al, 1995) revealed excellent inter-rater reliability in terms of kappa and Yule's Y coefficients for major mood and psychotic disorders (Preisig et al, 1999), and for SUD (Berney et al, 2002); the 6-week test-retest reliability was lower but still in the fair to good range (Berney et al, 2002;Preisig et al, 1999). The anxiety sections of the French version of the SADS-LA also revealed satisfactory inter-rater and test-retest reliability (Leboyer et al, 1991).…”
Section: Psychiatric Evaluationmentioning
confidence: 89%
“…The French version of this instrument also revealed adequate inter-rater and test-retest reliability for major mood (Preisig et al, 1999) and substance use disorders (Berney et al, 2002). The DIGS was completed with sections on generalized anxiety disorder and phobias using questions from the Schedule for Affective Disorders and SchizophreniaLifetime and anxiety disorder version (SADS-LA (Endicott and Spitzer, 1978)), which also revealed satisfactory test-retest reliability (Leboyer et al, 1991;Rougemont-Buecking et al, 2008). At baseline lifetime diagnoses and at follow-up the diagnosis of MDD since baseline were assigned according to the Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV) (American Psychiatric Association, 2000).…”
Section: Depression Status and Comorbid Mental Disordersmentioning
confidence: 98%